The effect of local non‐thermal plasma therapy on the cancer‐immunity cycle in a melanoma mouse model. Issue 3 (21st April 2022) - Lin, Abraham; De Backer, Joey; Quatannens, Delphine; Cuypers, Bart; Verswyvel, Hanne; De La Hoz, Edgar Cardenas; Ribbens, Bart; Siozopoulou, Vasiliki; Van Audenaerde, Jonas; Marcq, Elly; Lardon, Filip; Laukens, Kris; et al.
Abstract: Melanoma remains a deadly cancer despite significant advances in immune checkpoint blockade and targeted therapies. The incidence of melanoma is also growing worldwide, which highlights the need for novel treatment options and strategic combination of therapies. Here, we investigate non‐thermal plasma (NTP), an ionized gas, as a promising, therapeutic option. In a melanoma mouse model, direct treatment of tumors with NTP results in reduced tumor burden and prolonged survival. Physical characterization of NTP treatment in situ reveals the deposited NTP energy and temperature associated with therapy response, and whole transcriptome analysis of the tumor identified several modulated pathways. NTP treatment also enhances the cancer‐immunity cycle, as immune cells in both the tumor and tumor‐draining lymph nodes appear more stimulated to perform their anti‐cancer functions. Thus, our data suggest that local NTP therapy stimulates systemic, anti‐cancer immunity. We discuss, in detail, how these fundamental insights will help direct the translation of NTP technology into the clinic and inform rational combination strategies to address the challenges in melanoma therapy.